A revision of the Anthaxia (Haplanthaxia) kheiliana Obenberger, 1931 species-group (Coleoptera: Buprestidae) - Bílý, Svatopluk (Zootaxa, 2008)
Anthaxia (Haplanthaxia) kheiliana Obenberger, 1931 species-group is defined and revised, four new species are described: A. (H.) impressipennis, sp. nov. (Tanzania), A. (H.) nasheri, sp. nov. (Yemen), A. (H.) occulta, sp. nov. (Ethiopia, Kenya, Tanzania) and A. (H.) zambiana, sp. nov. (Zambia). All species are keyed and diagnostic characters of the group and all species are illustrated.